More Productive, Less Sustainable? On the Need to Consider Material Resource Flows - Anke Schaffartzik; Dominik Wiedenhofer; Marina Fischer-Kowalski (Intereconomics, 2016)
In environmental policymaking, the figurative cake that is wanted both to have and eat lies in achieving dematerialisation, i.e. reducing material resource use, and simultaneously pursuing a pathway lined with economic growth. Under such a scenario, we could have it all: increasing production and international convergence at the highest levels of consumption with a reduced impact on the environment in a lifestyle which could also be enjoyed by generations to come. In the following, we make a case for considering the evidence in contemplating the feasibility of such a utopia by taking social metabolism i.e. the material and energy input of society, into account.
Keywords: 330; Ressourcennutzung; Produktivitätsentwicklung; Materialfluss; EU-Umweltpolitik